IMPLEMENTATION OF REGENT REGULATION NUMBER 24 OF 2017 CONCERNING THE ESTABLISHMENT OF SERVICES WORK UNITS IN POPULATION ADMINISTRATION SERVICES IN PESISIR SELATAN REGENCY - Azharada, Ainov; Meiwanda , Geovani (Jurnal Administrasi Negara, 2022)
Through the implementation of Regency Regulation No. 24, 2017, about the Establishment of Service Work Units (UKL) in each sub-district in the affairs of population administration services in Pesisir Selatan Regency, the Pesisir Selatan Regency Government has endeavored to simplify and expand the range of population administration services. This study examined the implementation of policies through the lens of Edward III's theory of policy implementation, which is comprised of Communication, Resources, Disposition, and Bureaucratic Structure. Using interviews, observations, and documentation, a qualitative method was employed, and Interactive Model data analysis techniques were implemented in this study. According to the findings of this study, policy communication has been operating well. The UKL resource variable has adequate authority, but there are still limitations in the form of a restricted number of human resources, a lack of facilities, budgetary limits, and network issues. In the disposition variable, the attitude of the implementer has been supportive of the policy, but the pattern of bureaucratic appointments has not addressed credentials, and there are no incentives for UKL functional staff. In the bureaucratic structure variable already has the same SOP in supporting services, and the existence of fragmentation is accompanied by constant communication and coordination amongst implementers.